2010
DOI: 10.4314/ajtcam.v8i1.60511
|View full text |Cite
|
Sign up to set email alerts
|

Virologic And Immunologic Outcome Of Treatment Of Hiv Infectionwith A Herbal Concoction, Α-Zam, Among Clients Seeking Herbal Remedy In Nigeria

Abstract: This study was to determine the effectiveness (CD4 count and viral load) of a safe herbal concoction, α-Zam used by clients seeking herbal remedy for treatment of HIV infection in Nigeria. 51 patients taking α-Zam as complementary and alternative therapy through the herbal therapist were studied for a period of 16 months. Preliminary medical and laboratory examinations using WHO and CDC criteria were done after confirmation of HIV infection by Western blotting in the nearest teaching hospitals to the residence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
(21 reference statements)
1
8
0
Order By: Relevance
“…This patient sustained sero-reversion, avairaemia and normal CD4 count confirmed the earlier herbalist's claim that the concoction contained mainly Nigella sativa and honey (Onifade et al, 2011;Onifade et al, 2012;. Based on the findings from this HIV patient and others earlier documented evidences, the inference is that Nigella sativa and honey are the main constituents and other non-disclosed components are accelerating separation media.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This patient sustained sero-reversion, avairaemia and normal CD4 count confirmed the earlier herbalist's claim that the concoction contained mainly Nigella sativa and honey (Onifade et al, 2011;Onifade et al, 2012;. Based on the findings from this HIV patient and others earlier documented evidences, the inference is that Nigella sativa and honey are the main constituents and other non-disclosed components are accelerating separation media.…”
Section: Discussionsupporting
confidence: 86%
“…The role of honey as antimicrobial agent is not ambiguous but its effectiveness when combined with Nigella sativa in HIV infection was scantly documented. Nigella sativa and honey (main constituents of α-zam) was initially documented to have caused increase in CD4 count and decrease in viral load in HIV patients (Onifade et al, 2011). Previous studies and presentations of a herbal remedy (α-zam) that contained Nigella sativa and honey as the main constituents, other auxiliary constituents were not declared for public use by the herbal therapist (…”
Section: Introductionmentioning
confidence: 99%
“…There is recent policy for Pharmacovigilance of complementary medicine in Nigeria by the National Pharmacovigilance Centre (NPC), AbujaNigeria. There are many herbal remedies that are being used as complementary therapy to Highly Active Antiretroviral Therapy (HAART) in Nigeria [6], for example: Baissea axillaries Hua [7], Neem leaves [8], -Zam [9], Garlic, Ginger and Jobelyn. Studies in South Africa have shown that herbal remedies are good supplements to antiretroviral therapy because of their immune boosting properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…Globulin values were much higher in Lpv/r/GCHM group 42.17 g/L when compared to the control group 30.91 (p ≤ 0.05), which is suggestive of conditions such as dehydration, allergies, liver disease and stress. 15 Analysis of the haematological parameters indicated an increase in the WBC count 8.27 × 10 3 µL and 7.82 × 10 3 µL in groups V and VI compared to control 6.34 × 10 3 µL (p < 0.05) as shown in Table 3 where GCHM and Lpv/r was concomitantly administered. HCT was slightly increased in group VI 56.1% compared to the control 44.37% (p > 0.05), these values, however, were not statistically significant.…”
Section: Clinical Observationsmentioning
confidence: 89%